2012
DOI: 10.1016/j.jaapos.2011.12.149
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to occlusion therapy 3 months after cataract extraction in the Infant Aphakia Treatment Study

Abstract: Background Little information is available on factors that predict adherence to patching in infants. We evaluated data from the Infant Aphakia Treatment Study (IATS), a randomized clinical trial of treatment for infants with unilateral congenital cataracts, to investigate factors associated with successful adherence to patching protocols. Subjects and Methods In the IATS, patching was prescribed 1 hour daily per month of age until 8 months of age and 50% of waking hours thereafter. A centrally located staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Adherence was measured by using one of two report styles-either a 7-day prospective diary or a phone conversation requesting information on the previous 48 hours. In an earlier report, 18 we have shown that most caregivers describe being able to adhere to the prescribed occlusion treatment protocol within the first 3 months after surgery, and those parents whose child had private insurance report better adherence to the patching regimen. Additionally, an assessment of adherence to occlusion therapy in the first 6 months after cataract surgery and grating visual acuity at 12 months of age has demonstrated that better adherence results in better grating visual acuity.…”
Section: Discussionmentioning
confidence: 74%
“…Adherence was measured by using one of two report styles-either a 7-day prospective diary or a phone conversation requesting information on the previous 48 hours. In an earlier report, 18 we have shown that most caregivers describe being able to adhere to the prescribed occlusion treatment protocol within the first 3 months after surgery, and those parents whose child had private insurance report better adherence to the patching regimen. Additionally, an assessment of adherence to occlusion therapy in the first 6 months after cataract surgery and grating visual acuity at 12 months of age has demonstrated that better adherence results in better grating visual acuity.…”
Section: Discussionmentioning
confidence: 74%
“…If the level of uncertainty is too high and consequently the self‐efficacy too low, there is an imminent risk of the parents giving up the occlusion therapy and use of lenses and developing a sense of complete parental failure. This is an undesirable consequence, as previous research shows that patching is crucial for the child's visual status (Charters, ; Dixon‐Woods, Awan, & Gottlob, ; Drews‐Botsch, Hartmann, & Celano, ; Lundvall & Kugelberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that, in the first year after surgery, adherence to patching was associated with sociodemographic factors but not IOL implantation 11 and that adherence to patching in the first 6 months after surgery was associated with grating acuity at 12 months of age. 12 However, visual acuity measured behaviorally is not strongly predictive of optotype acuity. 13 Furthermore, adherence to patching may become more challenging as children begin to resist patching.…”
mentioning
confidence: 99%